Asymptomatic marginal zone lymphoma of mucosa-associated lymphoid tissue in the hypopharynx, detected with esophagogastroduodenoscopy. Issue 1 (1st January 2018) - Okada, Takuya; Kawada, Kenro; Sugimoto, Taro; Ito, Takashi; Yamaguchi, Kazuya; Kawamura, Yudai; Okuda, Masafumi; Kume, Yuichiro; Ryotokuji, Tairo; Hoshino, Akihiro; Tokairin, Yutaka; Nakajima, Yasuaki
Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma is a type of lymphoma that commonly originates in the gastrointestinal (GI) tract, and in rare instances may also occur in the head and neck region. In this report, we present a case of early stage, primary asymptomatic MALT lymphoma of the hypopharynx as detected by esophagogastroduodenoscopy (EGD). A 73-year-old man underwent EGD for an examination of the upper GI tract. At the left pyriform sinus, a swollen irregular mucosa was detected. Biopsy specimens confirmed histologically prominent proliferation of lymphocytes in the epithelium. Immunohistochemical analysis showed that the neoplastic lymphocytes were positive for CD20 and negative for CD3. Based on the other imaging studies, we diagnosed the lesion as a localized MALT lymphoma of the hypopharynx at Stage IA. In total, 46 Gy of radiotherapy was administered to the lesion. In the subsequent 5 years after the treatment, there have been no signs of recurrence.